Dairy animals and breast cancer: reflections on a long-term study from the 1970s that was never done. Issue 1 (17th February 2023) - Peaker, Malcolm
Abstract: In this short commentary I recall a long-term experiment that was sketched out to determine if the low incidence of mammary cancer in dairy animals reflects a low incidence in these species generally or is the result of a protective effect of early pregnancy and long lactations. Although that experiment was never done, I discuss these questions in the light of developing knowledge on the incidence of cancer in ruminants generally and in the mammary gland in particular.